2018
DOI: 10.1002/hep.30082
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Serum DNA andRNA Levels in Nucleos(t)ide Analog‐Treated or Untreated Patients During Chronic and Acute Infection

Abstract: Treatment of chronic hepatitis B (CHB) patients with nucleos(t)ide analogs (NAs) suppresses hepatitis B virus (HBV) DNA synthesis but does not affect synthesis of HBV pregenomic RNA (pgRNA). Hepatitis B virus pgRNA is detectable in the serum during NA treatment and has been proposed as a marker of HBV covalently closed circular DNA activity within the infected hepatocyte. We developed an automated assay for the quantification of serum HBV pgRNA using a dual-target real-time quantitative PCR approach on the Abb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
139
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(149 citation statements)
references
References 29 publications
9
139
1
Order By: Relevance
“…Therefore, the reported “HBV load” in NA‐treated subjects may vary from kit to kit that detects different regions of HBV DNA. Furthermore, as expected, but different from a recent report, the levels of serum HBV RNA are highest in the PreC/C region and declined from the S region to X region. Notably, HBV‐RNA level may also be affected by the RNA splicing‐variants given that some of them lack the S region, particularly after NA treatment .…”
Section: Discussioncontrasting
confidence: 84%
“…Therefore, the reported “HBV load” in NA‐treated subjects may vary from kit to kit that detects different regions of HBV DNA. Furthermore, as expected, but different from a recent report, the levels of serum HBV RNA are highest in the PreC/C region and declined from the S region to X region. Notably, HBV‐RNA level may also be affected by the RNA splicing‐variants given that some of them lack the S region, particularly after NA treatment .…”
Section: Discussioncontrasting
confidence: 84%
“…The QuantiGene assay developed by Lam et al uses HBV‐specific probes, designed to hybridize with the X open reading frame (ORF), to enable direct quantification of RNA without cDNA synthesis or PCR amplification . Recently, Butler et al developed an automated high‐throughput assay to quantify serum HBV RNA, which was isolated using RNA selective extraction chemistry (Abbott mSample Preparation System), followed by a multiplex quantitative RT‐PCR procedure for detecting amplicons of hepatitis B X and core region on the m2000 platform (Abbott Molecular) . To further evaluate the automated prototype assay performance, Butler et al conducted a comparative testing of flRNA and found a good correlation between these two methods.…”
Section: Serum Hbv Rna Species and Measurementmentioning
confidence: 99%
“…Our previous study showed that CHB patients could achieve HBeAg seroconversion when their HBV RNA levels were below 4.12 log 10 copies/mL before treatment . Another study found a weak correlation between the HBV DNA and pgRNA levels during NA therapy . High serum pgRNA often reflects reverse transcription failure .…”
Section: Introductionmentioning
confidence: 99%